Analisis Pemahaman Matematis Siswa pada Materi Trigonometri - Fina Farhatul Kamalia; Mochamad Abdul Basir; Nila Ubaidah (Universitas Sarjanawiyata Tamansiswa, 2020)
In this research, the writer analyzes about students' mathematical comprehension skill. The aim of this research is to know students' mathematical comprehension skill at trigonometry lesson especially in quantity and two angles deviation session. The indicator in this research are students' computational comprehension skill and functional comprehension skill. The type of the research is descriptive qualitative research by using test interview and documentation as the data collection technique. The subject of the research are 34 students of XI Science Education Class 6 MA N 1 Semarang. The result are: (1) computational comprehension skill 81.25% is included to understand category. This case shows that some students have understood the use of the formula and the appropriate concept. (2) Functional comprehension skill 86.02% is included to very understand. Most of students have understood the questions and students are able to connect the questions with the other concepts. The results of interviews with students showed that there were some students who stated that they were still confused when they encountered questions that were slightly different from the examples or those taught, but some students had no difficulty in completing the test questions given.